Mucosal-Pull Induction of Lung-Resident Memory CD8 T Cells in Parenteral TB Vaccine-Primed Hosts Requires Cognate Antigens and CD4 T Cells - Haddadi, Siamak; Vaseghi-Shanjani, Maryam; Yao, Yushi; Afkhami, Sam; D'Agostino, Michael R.; Zganiacz, Anna; Jeyanathan, Mangalakumari; Xing, Zhou (Frontiers in Immunology, 2019)
Tissue resident memory T cells (TRM) are critical to host defense at mucosal tissue sites. However, the parenteral route of immunization as the most commonly used immunization route in practice is not effective in inducing mucosal TRM cells particularly in the lung. While various respiratory mucosal (RM)-pull strategies are exploited to mobilize parenteral vaccine-primed T cells into the lung, whether such RM pull strategies can all or differentially induce Ag-specific TRM cells in the lung remains unclear. Here we have addressed this issue by using a parenteral TB vaccine-prime and RM-pull model. We show that both Ag-independent and Ag-dependent RM pull strategies are able to mobilize Ag-specific CD8 T cells into the lung. However, only the RM pull strategy with cognate antigens can induce robust Ag-specific CD8 TRM cells in the lung. We also show that the cognate Ag-based RM pull strategy is the most effective in inducing TRM cells when carried out during the memory phase, as opposed to the effector phase, of T cell responses to parenteral prime vaccination. We further find that cognate Ag-induced CD4 T cells play an important role in the development of CD8 TRM cells in the lung. Our study holds implications in developing effective vaccine strategies against respiratory pathogens.